Phenolic compound profiles and their seasonal variations in new red-phenotype head-forming Chinese cabbages. (April 2018) - Lee, Hyeyoung; Oh, Il-Nam; Kim, Jungeun; Jung, Dahan; Cuong, Nguyen Phu; Kim, Younmi; Lee, Jongcheol; Kwon, Oha; Park, Sang Un; Lim, Yongpyo; Kim, Byungjoo; Park, Jong-Tae
Abstract: In previous study, red Chinese cabbages which satisfy the morphological characteristics of traditional Chinese cabbages were developed by crossing Chinese cabbage and red cabbage, with subsequent backcrossing. In this study, we evaluated the phenolic compound profiles of two newly developed red-phenotype Chinese cabbages in comparison with three typical cultivars. Anthocyanidins (cyanidin), phenolic acids (caffeic acid, p -coumaric acid, ferulic acid, and sinapic acid), and flavonols (quercetin and kaempferol) were identified and quantified by HPLC, LC/MS and LC/MS/MS analyses. The new cultivars contained significantly increased levels of phenolic compounds, except for kaempferol. Their contents drastically varied by sowing season. The spring-sown red Chinese cabbages contained significantly higher levels of phenolic acids (11, 530 and 12, 437 μg/g dry wt.) and cyanidin (1830 μg/g dry wt.) but lower levels of flavonols than their fall-sown counterparts. Correlation analysis exhibited a significant positive correlation between cyanidin and phenolic acids but a negative correlation between phenolic acids and flavonols in red Chinese cabbages. Principal component analysis could differentiate red Chinese cabbages and typical cultivars with different sowing seasons based on their phenolic compound profiles. This study provides information regarding the selection of appropriate Chinese cabbage cultivars rich in phenolic compounds that may benefit human health. Highlights: Newly developed red Chinese cultivars contained significantly increased levels of phenolic compounds. Spring-sown red Chinese cabbages contained higher levels of phenolic acids and cyanidin than their fall-sown counterparts. Developed red cultivars can be used as raw materials for further industrial application.